Origin and Processing Methods Slightly Affect Allergenic Characteristics of Cashew Nuts (Anacardium occidentale). Issue 4 (10th March 2018) - Reitsma, Marit; Bastiaan‐Net, Shanna; Sijbrandij, Lutske; de Weert, Evelien; Sforza, Stefano; Gerth van Wijk, Roy; Savelkoul, Huub F. J.; de Jong, Nicolette W.; Wichers, Harry J.
Abstract: The protein content and allergen composition was studied of cashews from 8 different origins (Benin, Brazil, Ghana, India, Ivory Coast, Mozambique, Tanzania, Vietnam), subjected to different in‐shell heat treatments (steamed, fried, drum‐roasted). On 2D electrophoresis, 9 isoforms of Ana o 1, 29 isoforms of Ana o 2 (11 of the acidic subunit, 18 of the basic subunit), and 8 isoforms of the large subunit of Ana o 3 were tentatively identified. Based on 1D and 2D electrophoresis, no difference in allergen content (Ana o 1, 2, 3) was detected between the cashews of different origins ( P > 0.5), some small but significant differences were detected in allergen solubility between differently heated cashews. No major differences in N‐ and C‐terminal microheterogeneity of Ana o 3 were detected between cashews of different origins. Between the different heat treatments, no difference was detected in glycation, pepsin digestibility, or IgE binding of the cashew proteins.